2019
DOI: 10.1097/jbr.0000000000000035
|View full text |Cite
|
Sign up to set email alerts
|

Hidden hearing loss: current perspectives and potential therapies

Abstract: Hidden hearing loss (HHL), an auditory dysfunction that has gained much recent attention, has the hallmarks of speech discrimination and intelligibility deficits with normal or near-normal hearing thresholds. The pathological mechanisms of HHL are complicated and are not yet fully understood. HHL can be resulted from disorders of the central nervous system such as auditory cortex, and/or pathological changes of inner ear. Thus far, 2 pathological phenomena, synaptopathy and auditory nerve demyelination, have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Moreover, PTA has a limited relationship with the lived experience of disability (Demeester et al, 2012), especially self-reported comprehension in noisy environments (Kramer et al, 1996) or group conversations (Gatehouse & Noble, 2004). Thus, PTA fails to capture "hidden hearing loss": individuals with normal hearing thresholds who have deficits in speech discrimination and intelligibility (Chen et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, PTA has a limited relationship with the lived experience of disability (Demeester et al, 2012), especially self-reported comprehension in noisy environments (Kramer et al, 1996) or group conversations (Gatehouse & Noble, 2004). Thus, PTA fails to capture "hidden hearing loss": individuals with normal hearing thresholds who have deficits in speech discrimination and intelligibility (Chen et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…First, as discussed previously, the hearing measure we use is a limitation as subjective hearing reports may vary by demographic characteristics (Kamil et al, 2015). However, PTA is also subject to limitations especially when it comes to capturing the difficulties that individuals experience in their everyday lives (Chen et al, 2019;Demeester et al, 2012;Gatehouse & Noble, 2004;Kramer et al, 1996). Self-rated hearing is the only measure available in the HRS.…”
Section: Limitationsmentioning
confidence: 99%